An analytical failure model for pressurized blister tests of thermally loaded composite laminates. (1st June 2021) - Hübsch, Jan David; Rosendahl, Philipp Laurens; Mittelstedt, Christian
Abstract: An analytical finite fracture mechanics model for pressurized blister tests is developed. This paper describes in detail governing equations, solution procedure and stress analysis. The stress solution and incremental energy release rate show good accordance to Finite Element Analysis. The derived failure model is discussed in the context of pressurized blister tests. The blister tests are performed at different temperatures between − 40 ° C and 100 ° C published by the authors in a previous article. The failure model describes different gap widths with adequately assumed temperature-dependent elastic and strength properties over a wide temperature range. Graphical abstract: Image 1 Highlights: Finite fracture mechanics model for pressurized blister tests. Stress solution derived from an interface model based on first-order shear deformation theory. Validation with test results at different temperatures.